Multiplex assay to identify Korean vectors of malaria - Joshi D. (2014)
Following the recent emergence of malaria in South Korea, vector control has been an important task. For this, vector identification is very important. Earlier, two PCR-based assays have been described. But, poor species resolution and their ability to include only 4-5 species limit their use. Thus, it has now become important to revise the assay identifying these members. In this study, a new assay based on internal transcribed spacer 2 and 28S of ribosomal DNA has been described. The assay successfully identified all the Korean malaria vector mosquitoes. Therefore, it is an indispensable tool to study ecology, abundance and biology of these species. © 2010 Blackwell Publishing Ltd.